2016
DOI: 10.1097/md.0000000000003674
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Outcomes, and Risk Factors of Community-Acquired and Hospital-Acquired Acute Kidney Injury

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
71
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 29 publications
12
71
2
Order By: Relevance
“…Short-and long-term mortality is increased in CA H -AKI [1,8] although HA-AKI is more likely to result in death [3,10,11] . Talabani et al [5] reported 45% 3-year mortality for CA H -AKI compared to 15.7% ( p < 0.01) in the control cohort with similar figures reported at 5 years (44.6% in Soto et al [7] ).…”
Section: Resultsmentioning
confidence: 99%
“…Short-and long-term mortality is increased in CA H -AKI [1,8] although HA-AKI is more likely to result in death [3,10,11] . Talabani et al [5] reported 45% 3-year mortality for CA H -AKI compared to 15.7% ( p < 0.01) in the control cohort with similar figures reported at 5 years (44.6% in Soto et al [7] ).…”
Section: Resultsmentioning
confidence: 99%
“…Even as a relatively new study concept, several risk factors for CA-AKI have been identified, many of which are reflective of those for HA-AKI, such as age, diabetes, congestive HF, CKD, human immunodeficiency virus, obstructive uropathy, and volume depletion [1, 9]. Patients with CA-AKI are more likely to have comorbidities than patients with HA-AKI [17]. The most common etiology of CA-AKI is typically prerenal, such as gastrointestinal loss, poor intake, and/or medications such as nonsteroidal anti-inflammatory drugs, diuretics, and/or angiotensin-converting enzyme inhibitors [18].…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies have focused on the epidemiology and clinical outcomes of patients who developed AKI during hospitalization—hospital‐acquired (HA)‐AKI—little is known about community‐acquired (CA)‐AKI (before hospitalization); nine studies have examined it . CA‐AKI was actually about two to four times more common than HA‐AKI.…”
Section: Epidemiology Of Akimentioning
confidence: 99%
“…Five studies investigated the need for acute dialysis in patients with CA‐AKI and HA‐AKI . All but one study showed that HA‐AKI patients were twice as likely to need acute dialysis.…”
Section: Epidemiology Of Akimentioning
confidence: 99%